Personal Information Sharing Behavior Using Social Media - Ashraf Sharif; Shafiq Ur Rehman; Khalid Mahmood (Journal of Information Management and Practices)
This study explores personal information sharing behavior publication patterns and trends on social media from 2007-2024 with an aim to highlight the annual growth of personal information sharing behavior (PISB) on social media platforms, key patterns in the PISB literature in terms of frequently cited authors, countries, institutions, sources, highly cited papers, collaboration and authorship patterns, thematic evolution, keyword and key factor analysis (such as countries, sources, and keywords). We used Scopus database for data extraction, and 1020 pertinent records were chosen. The data was evaluated with Microsoft Excel, Access, Biblioshiny and VOSviewer software. The United States of America is leading in a top authors, organizations and as a country on PISB literature. This authorship pattern trends revealed that the authors on PISB literature prefer to work with two, three, four or as a single author and they give low preference to work with more than four authors. The country-level collaboration trend revealed that the collaboration between United States and China are the most frequently occurring among the rest of other countries. Thematic evolution identified that some themes become obsolete, and some emerge with the passage of time. However, notably, the recent period (2021-2024) is mainly connected with various social media issues and challenges. The three-factor (keywords, countries and sources) revealed that the researchers of top countries used mostly six keywords (self-disclosure, social media, privacy, Facebook, social networking sites, and social support) and they preferably published in two major sources. This finding shows that the authors from the top ten countries mainly published their work in highly selected journals.